Better Use of Data to improve parent Satisfaction (BUDS): protocol for a prospective before-and-after pilot study employing mixed methods to improve parent experience of neonatal care - Neena Modi; Chris Gale; Mehali Patel; Thomas Woodcock; Derek Bell; Susanna Sakonidou; Izabela Andrzejewska; Sophia Kotzamanis; Wendy Carnegie; Mable Nakubulwa; Lucy Culshaw; Kelvin Dawson; et al. (BMJ Publishing Group, 2019)
Introduction Having a baby that requires neonatal care is stressful and traumatic. Parents often report dissatisfaction with communication of clinical information. In the UK neonatal care data are recorded daily using electronic patient record systems (EPR), from which deidentified data form the National Neonatal Research Database (NNRD). We aim to evaluate the impact of sharing neonatal EPR data with parents, on parent-reported satisfaction, parent-staff interactions, staff workload and data completeness.Methods A prospective, before-and-after, mixed-method study. Participants are parents of inpatient babies (maximum 90) and staff in a tertiary neonatal intensive care unit, London, UK. The intervention was developed by former neonatal parents, neonatologists and neonatal nurses: a communication tool for parents comprising individualised, written, daily infant updates for parents, derived from EPR data. The intervention will be provided to parents over 6 weeks. Plan-Do-Study-Act cycles will inform the tool's iterative development and improvement. The tool's impact will be measured using a validated parent survey, staff survey, data completeness measures and interviews.Analysis Primary outcome: parent satisfaction 'with communication of clinical information and involvement in care'. Secondary outcomes: parent-staff interactions, staff workload, data completeness. Baseline survey data will be obtained from clinical service evaluation preceding the intervention. Baseline data completeness will be derived from the NNRD. During the intervention, surveys will be administered biweekly and data completeness assessed daily. We will analyse outcomes using run charts and partially paired statistical tests. Parent and staff interviews will explore information exchange and the communication tool's impact.Discussion This study will evaluate the impact of a parent co-designed intervention on communication with parents in neonatal care and the completeness of routinely recorded electronic clinical data. Better use of routinely recorded clinical data provides the opportunity to improve parent satisfaction and increase the research utility of such data, benefiting clinical care.Ethics and dissemination Reviewed and approved by the West Midlands-South Birmingham REC (18/WM/0175).Registration number ISRCTN62718241.